FBR Human Resource Management Policy: Issues and Challenges, Suggested Policy Interventions to Increase Productivity - Jawwad, Abdul (Journal of Pakistan Administration, 2025)
The Federal Board of Revenue (FBR) is the premier revenue collecting agency of the country. The performance of FBR has always remained under the spotlight. In view of the burgeoning budget deficit it has become the center stage of the Government efforts to turn around the economy. Efforts are afoot to increase the productivity of the organization which in turn is measured by parameters like growth in revenue and tax to Gross Domestic Production (GDP) Ratio. Measures to enhance the productivity of FBR more often than not comprise of increasing the tax rates, strengthening enforcement, selecting larger number of cases for audit, broadening of tax base, automating the systems and reinforcing the law. Optimal performance of the FBR depends on many factors. Human Resource Management (HRM) is one such factor which could not grasp the full attention of the policy makers.
Keywords: FBR; Human Resource Management Policy; Issues and Challenges; Policy Interventions; Productivity